Management of Zygomatico maxillary complex fractures with two-point fixation-A retrospective study for 5 years - Shanmugam, Devakumari; Thanasekaran, Vijhayapriya; Biradar, Nandini; Purushothaman, Amudha; Sridhar, Dinesh; Shanmugam, Devameena (Asian Journal of Medical Sciences, 2021)
Background: The Zygomatico maxillary complex fractures (ZMC) are commonly encountered in the practice of the maxillofacial surgeon. Perfect management of the fracture is absolutely essential as the revision surgeries are tedious. Surgical management of ZMC is done at two or three points depending on the clinical displacement.Aims and Objectives: Zygomatico maxillary complex is the second most common fractures next to nasal bone fracture in the face worldwide. ZMC fractures are frequently seen and they were managed in great volumes throughout the country. The aim of our study is to prove the surgical outcomes of two-point fixation in the management of ZMC fractures.Materials and Methods: The inpatient records follow up records, radiographic records and photographs of 55 patients who underwent management of ZMC with two point fixations (one at zygomatic buttress and one at the fronto zygomatic region) were retrieved and analysed for the surgical outcomes. The evaluation was done preoperatively and postoperatively at 4weeks, 8 weeks and 12 weeks.Result: Two-point fixations give stable results both aesthetically and functionally in the management of Zygomatico maxillary complex fractures.Conclusion: Rigid internal fixation with titanium miniplates at two points in zygomatic buttress and in the fronto zygomatic region can be adopted with confidence as it gives excellent results. The scar formed in the infraorbital region or the unsightly ectropion can be avoided by not including the infra orbital region.